Analisis Kandungan Merkuri Pada Air Sungai Ongkag Mopusi Di Desa Tanoyan Selatan Mengunakan AAS - Mokoginta, Meki; Pongoh, Emma; Saiya, Abdon (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Environmental pollution relates to exposure to pollutants that disrupt the natural environment and can affect living things in the environment. One of the most dominant pollutants in the mining business is heavy metals such as mercury (Hg) which is classified as a hazardous toxic material. The purpose of this study was to measure the levels of mercury (Hg) contained in samples of Ongkag Mopusi River water in South Tanoyan village using AAS. Based on the results of research on Ongkag Mopusi river water samples in South Tanoyan Village using Atomic Absorption Spectrophhotometer (AAS), the lowest Hg exposure was obtained at point B3 of 0.00002 ppm and the largest at 0.0001 ppm. from these results it is concluded that Ongkag Mopusi river water in South Tanoyan Village is still in accordance with the quality standards set by Government Regulation No. 82 of 2001 concerning Water Quality Management and Pollution Control, where the allowable mercury threshold for category I water is 0.001 mg/L.